2009
DOI: 10.1007/s11240-009-9577-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant growth regulators on ovary culture of coconut (Cocos nucifera L.)

Abstract: Coconut is a cross pollinating palm, propagated only by seeds. Tissue culture is the only vegetative propagation method available for coconut. Consistent callogenesis was obtained by culturing unfertilised ovaries at -4 stage in CRI 72 medium containing 100 lM 2,4-dichlorophenoxyacetic acid (2,4-D) and 0.1% activated charcoal. Callusing was improved by application of 9 lM thidiazuron (TDZ). Embryogenic calli were subcultured onto somatic embryogenesis induction medium containing 66 lM 2,4-D. Stunted growth was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 43 publications
0
11
0
3
Order By: Relevance
“…A high auxin concentration in association with activated charcoal has been widely used in the induction of somatic embryogenesis of palm species (Pérez-Nuñez et al 2006;Saénz et al 2006;Steinmacher et al 2007b;Othmani et al 2009;Perera et al 2009;Al-Khayri 2010). For A. aculeata, Moura et al (2009) showed that activated charcoal was essential for avoiding tissue browning and stimulating somatic embryo formation.…”
Section: Discussionmentioning
confidence: 99%
“…A high auxin concentration in association with activated charcoal has been widely used in the induction of somatic embryogenesis of palm species (Pérez-Nuñez et al 2006;Saénz et al 2006;Steinmacher et al 2007b;Othmani et al 2009;Perera et al 2009;Al-Khayri 2010). For A. aculeata, Moura et al (2009) showed that activated charcoal was essential for avoiding tissue browning and stimulating somatic embryo formation.…”
Section: Discussionmentioning
confidence: 99%
“…According to Garcia and co-workers (2007), light can modulate the action of different growth regulators inducing various morphogenic responses. ABA has been found to adversely affect shoot regeneration in Cocos nucifera (Perera et al 2009). This hormone also inhibited regeneration of Medicago sativa somatic embryos (Kępczyńska and Zielińska 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It occurs in the palm family (Arecaceae) and is the sole species of the genus Cocos within the subfamily Arecoideae which also contains other economically important species including date palm and oil palm [4]. Prasanthi Perera, et al [6] add that it is a cross-pollinating palm, propagated only by seeds, whilst tissue culture is the only vegetative propagation method available for coconut. According to the description of the coconut tree, it has many names based on its taxonomic hierarchy as shown below (Table 1).…”
Section: Characteristics Of Coconut Plants In Tropical Coastal Regionsmentioning
confidence: 99%